Examining Stock Market Co-Movement In The Pre, During, And Post-Covid Eras In Developing And Developed Markets - Mr. Muhammad Adnan , Dr. Jawad Karamat , Ms. Sadaf Ambreen , Muhammad Subhan , Dr. Arooj Zeb , Mr. Adnan Khan (Migration Letters, 2024)
The COVID-19 epidemic disrupted global financial markets, requiring a thorough analysis of its effects on stock markets in underdeveloped and developed countries. The pre-COVID era (March 1, 2019, to February 28, 2020) provides a crucial baseline for market conditions before the pandemic. The during (March 1, 2020, to February 28, 2021) illuminates the crisis’s immediate and tumultuous market responses. The post-COVID phase (March 1, 2021, to February 28, 2023) provides a critical vantage point to evaluate market recovery and long-term consequences as[1] economies adapt to the ’new normal.’ Our research uses mean returns, standard deviations, variances, skewness, and kurtosis to provide return data distribution details. Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) unit root tests carefully evaluate time series data stationarity, revealing stock market resilience during difficult periods. This research provides a nuanced view of stock market reactions across locations and periods. These findings are crucial for politicians, investors, and academics navigating complex financial markets during unprecedented global crises. This research illuminates how to succeed in an ever-changing economic environment as financial markets change and face new difficulties. Our study helps us understand financial market behavior during crises, enabling educated decision-making and strategic planning in an uncertain time.